Inborn Errors of Metabolism - Erich Maul (Association of American Medical Colleges, 2009)
Abstract Understanding metabolic disease can be difficult in its own right. Under stressful situations such as those involving a sick infant, it becomes much more difficult. This resource is a talk whose purpose is to provide a simple framework with which to expeditiously diagnose a sick child who has a metabolic disorder. This talk was originally given to third-year medical students and residents on the pediatric wards after the presentation of a child with medium chain acyl-CoA dehydrogenase deficiency. The basic, broad concepts the talk defines were well received by the housestaff and were helpful in framing their future evaluations of suspected metabolic disease. The talk is published here as a PowerPoint file with an attached script that a lecturer can print out in order to have notes for presentation. There is no pretest or posttest. The main focus of the talk is to help pediatric care providers gain a basic framework for when and how to evaluate a suspected inborn error of metabolism in a child. The talk features very little detail about specific inborn errors, which are beyond the scope of the presentation.